Systematic review on post-stroke computerized cognitive training: Unveiling the impact of confounding factors - Fava-Felix, Paloma E.; Bonome-Vanzelli, Silvia R. C.; Ribeiro, Fabiana S.; Santos, Flávia H. (Frontiers in Psychology, 2022)
Background Stroke is a highly incapacitating disease that can lead to disabilities due to cognitive impairment, physical, emotional, and social sequelae, and a decrease in the quality of life of those affected. Moreover, it has been suggested that cognitive reserve (patients’ higher levels of education or having a skilled occupation), for instance, can promote faster cognitive recovery after a stroke. For this reason, this review aims to identify the cognitive, functional, and behavioral effects of computerized rehabilitation in patients aged 50 years or older who had a stroke, considering cognitive reserve proxies. Methods We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis—PRISMA, and performed the search for peer-reviewed randomized controlled trials without a date restriction on CINAHL, LILACS, PubMed, Scopus, and Web of Science databases were chosen. Results We screened 780 papers and found 19 intervention studies, but only 4 met the inclusion criteria and shared data. These studies included computerized tools for motor and cognitive rehabilitation in the experimental groups. In all studies, computerized training was combined with other interventions, such as standard therapy, occupational therapy, and aerobic exercises. There were 104 participants affected by ischemic or hemorrhagic stroke, predominantly male (57.69%), and all with cognitive impairment. Conclusion Despite a limited number of studies, varied methods and insufficient information available, schooling as a CR proxy combined with high-intensity computerized cognitive training was key to mediating cognitive improvement. The systematic review also identified that the associated ischemic stroke and shorter time of onset for rehabilitation contribute to the cognitive evolution of patients. Findings do not support a greater benefit of computerized cognitive training compared to conventional cognitive therapies. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=296193], identifier [CRD42022296193].